Third world approaches to international law : on praxis and the intellectual / edited by Usha Natarajan, John Reynolds, Amar Bhatia and Sujith Xavier. - Natarajan, Usha; Reynolds, John, 1981-; Bhatia, Amar; Xavier, Sujith, 1977- (Abingdon, Oxon, : Routledge, Taylor & Francis Group, 2018)
This book addresses the themes of praxis and the role of international lawyers as intellectuals and political actors engaging with questions of justice for third world peoples. The book brings together 12 contributions from a total of 15 scholars working in the TWAIL (Third World Approaches to International Law) network or tradition. It includes chapters from...third world jurists who have led this field since the time of decolonization, as well as prominent emerging scholars in the field. Broadly, the TWAIL orientation understands praxis as the relationship between what we say as scholars and what we do - as the inextricability of theory from lived experience. Understood in this way, praxis is central to TWAIL, as TWAIL scholars strive to reconcile international law's promise of justice with the proliferation of injustice in the world it purports to govern. Reconciliation occurs in the realm of praxis and TWAIL scholars engage in a variety of struggles, including those for greater self-awareness, disciplinary upheaval, and institutional resistance and transformation. The...contributions in the book engage these themes and questions through the various prisms of international institutional engagement, world trade and investment law, critical comparative law, Palestine solidarity and decolonization, judicial education, revolutionary struggle against imperial sovereignty, Muslim Marxism, third world intellectual traditions, global South constitutionalism, and migration.'--
'The chapters in this book were originally published in Third World Quarterly, volume 37, issue 11 (2016)'--Page ix.
Includes bibliographical references and index.
Keywords: International law -- Developing countries -- Congresses